The effects of different shift patterns on nurses' sleep-wake behaviours in selected, private healthcare facilities - Bell, Emma Catherine (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Nurses are required to work shifts to provide 24-hour care, in which they complete physically and mentally demanding tasks. The length and type of shifts, particularly night shifts interfere with the natural sleep-wake behaviours, leading to extended wakefulness and overall reduced sleep, and increase the likelihood of sleepiness during subsequent shifts. This can in turn affected various cognitive processes such attention, vigilance and alertness, which are necessary during the care process. Sleepiness as a result of working shifts has also been associated with an increased risk accidents and error during the delivery of care. Given the unique demands and ways in which workplaces are structured, each context arranges its shifts in unique ways and thus, in order to determine how to manage the effects of shift work, it is important to understand how it affects self-reported fatigue and sleep, of, in this case, nurses. While there has been extensive research on this in the global north, to date, there has been limited research aimed at examining the effects of shift work on nurses' sleep-wake behaviours and fatigue in the South African context. Therefore, the aim of this study is to characterise shift arrangements in selected private facilities and explore its effects on private healthcare nurses. This study adopted a cross-sectional, survey design using an amended version of Standard Shiftwork Index. The questionnaire included demographic and shift details and explored the impact of the shift systems on nurse sleep-wake behaviours and disturbances and fatigue and workload. It was distributed among shift working nurses registered with the South African Nursing Council across three selected, private, healthcare facilities in the Eastern Cape, over a two-month period. The responses were analysed with descriptive and inferential statistics, with open-ended questions analysed using a thematic analysis. A total of 51 nurses completed the survey. Nurses worked 12-hour shifts which included night shifts and day shifts with fixed start and end times. Over time was commonly reported and generally, nurses reported having very little control over their shift arrangements. Overall, nurses slept less than what they reported they needed on duty days, with nurses working both day and night shifts reporting to sleep less than the globally recommended required sleep. This was compensated for by longer sleep durations during days off. The data collection revealed that three different shift arrangements were in use, including permanent day shifts, permanent night shifts and rotating shift work including nights, with permanent night nurses working significantly more consecutive shifts (seven) than the other two shift types and having significantly more days off (seven) as well. While there were no significant differences in self-reported sleep across the three shift types, permanent night nurses were found to have the shortest sleep. During days off, rotating nurse reported significantly longer sleep times compared to day shift workers which may point to the need to catch up from sleep debt. Rotating nurses experienced the greater total disturbances to their sleep than permanent day and permanent night shift nurses. While not statistically significant, it may point to the fact that rotating shift workers could not obtain regularly timed sleep (due to having to change their schedules) compared to permanent day and night nurses. Workload (physical, emotional, mental and time pressure) did not differ between the shifts (day or night) or the shift types, but did reflect a heavier workload, possibly due to the data collection occurring during the 5th wave of the COVID 19 pandemic. This study highlights that nurses in private healthcare facilities are working extended hours which were associated with reduced total sleep, irrespective of the nature of the shift, with rotating shift nurses experiencing some degree of greater disturbances to their sleep. The number, duration speed and direction of the shifts of rotating nurses needs to be explored further, whilst also exploring the influence of individual factors on sleep-wake behaviours of nurses. It may be beneficial for the healthcare facilities to implement fatigue management strategies to mitigate the negative impacts of shift work, given the impact that this may impact the delivery of care.
Keywords: Fatigue; Fatigue in the workplace; Sleep deprivation; Sleep-wake cycle; Shift systems; Nurses; Health facilities, Proprietary